Assessing statewide water utility affordability at the census tract scale. Issue 3 (7th June 2022) - Van Abs, Daniel J.; Evans, Tim; Irby, Kimberley
Abstract: Academic and government research regarding the affordability of household drinking water and sewer utility (water utility) costs have resulted in the development of several methodologies that have been tested at various geographic levels. A New Jersey study on potential household affordability stresses from water utility costs at or below the Census tract‐level estimates that approximately one‐fifth of all New Jersey households could face affordability stresses, assuming that they directly pay all water utility costs. The methodology is adapted from the Affordability Ratio method of Teodoro. The results show the potential for use of county‐level household essential expenditure estimates in areas with high‐density populations. They also show the value of the methodology as a basis for policy discussions regarding the severity and geographic distribution of affordability stresses, as the analysis clearly indicates that significant affordability stresses exist in many suburban municipalities and rural town centers, not just historic urban cities.